Collaborative behaviour and coalitions in male jaguars (Panthera onca)—evidence and comparison with other felids - Włodzimierz Jędrzejewski; Rafael Hoogesteijn; Allison L. Devlin; Fernando Tortato; Henrique Villas Boas Concone; Fernando Azevedo; Charlotte E. Eriksson; Carlos Eduardo Fragoso; Maria Abarca; Ronaldo G. Morato; Anthony J. Giordano; Almira Hoogesteijn; et al. (Behavioral Ecology and Sociobiology, 2022)
Most large felids are classified as solitary species, with only lions ( Panthera leo ) and cheetahs ( Acinonyx jubatus ) exhibiting social, collaborative behaviours. Herein, we present evidence of the formation of male coalitions by jaguars ( Panthera onca ), based on data from five studies conducted with camera trapping, GPS telemetry, and direct observations in the Venezuelan Llanos and Brazilian Pantanal. Out of 7062 male records obtained with camera traps or visual observations, we detected 105 cases of male-male interactions, of which we classified 18 as aggression, nine as tolerance, 70 as cooperation/coalition, and eight as unidentified. In two studies, two male jaguars formed stable coalitions lasting over 7 years each. In the Llanos, each coalition male paired and mated with several females. For male jaguar coalitions, we documented similar behaviours as recorded earlier in lions or cheetahs, which included patrolling and marking territory together, invading territories of other males, collaborative chasing and killing other jaguars, and sharing prey. However, different from lions or cheetahs, associated male jaguars spent less time together, did not cooperate with females, and did not hunt cooperatively together. Our analysis of literature suggested that male jaguar coalitions were more likely to form when females had small home range size, a proxy of females’ concentration, while in lions, the male group size was directly correlated with the female group size. Similarly, locally concentrated access to females may drive formation of male coalitions in cheetahs. We conclude that high biomass and aggregation of prey are likely drivers of sociality in felids. Significance statement The division into social and solitary species in large felids has so far seemed unambiguous, with only lions and cheetahs classified as social species, in which male coalitions also occurred. Our data show that, under certain conditions, male coalitions may also form in jaguar populations. Factors that drive formation of male coalitions in lions and cheetahs, but not in other species of large cats, have not been clear until now. Our analyses indicate that in jaguars, lions, and cheetahs, the concentration of females likely plays the most important role. In jaguars, the probability of male coalition occurrence is highest in populations with the smallest mean female home range size (and thus likely high local density of females), while in lions, male group size is most strongly correlated with female group size.